The necessity of using baseline data to determine balance recovery post-concussion during the asymptomatic phase. Issue 11 (25th May 2017) - Fedy, Laura; Cinelli, Michael
Abstract : Objective: To determine whether sensory manipulation balance testing was able to detect balance control impairments in previously concussed asymptomatic (PCA) athletes. We hypothesised that PCA athletes would have balance control deficits in the A/P direction with sensory manipulations. Participants: 27 female athletes (19.78±1.3 years); 13 were previously concussed (PC) within the past 12 months and 14 had no history of concussions (NC). Design: Manipulation of visual, somatosensory, and vestibular contribution to balance control within the following trials: 3 eyes open (EO); 3 eyes closed (EC); 1 dual-task arithmetic (DUAL); compliant surface with eyes open (EOc) and eyes closed (ECc); 1 horizontal eye movement task (VOR); and 1 horizontal head turns with EC (HHT). Participants tested prior to the start of season; four of them sustained a concussion during the season and were retested following the resolution of symptoms (i.e., RTP-2). Procedures: Participants stood for 45s on a Bertec force plate (collected at 100Hz) in a Romberg stance. Trials were presented in order of increasing difficulty: EO1, EC1, dual task, EOc, ECc, VOR, EO2, EC2, HHT, EO3, and EC3. Data analysis: Root mean square (RMS) of centre of pressure displacement and velocity (dCOP and vCOP) were calculated in the A/P and M/L directions. Statistical analysis: Independent (PC vs. NC) and paired (baseline vs. RTP-2) t-tests were performed for each condition in both directions for dCOP and vCOP. Main results: HHT condition revealed that A/P vCOP RMS (mm/s) was significantly greater in PC (Mean Diff=2.63, p=0.02) and within at RTP-2 (Mean Diff=5.24, p=0.02). Conclusions: Balance impairments exist up to 12 months post-concussion in PCA athletes when their vestibular systems were perturbed (HHT) and higher-order analyses (vCOP) were calculated. Competing interests: None.